Karyopherin α2-dependent import of E2F1 and TFDP1 maintains protumorigenic stathmin expression in liver cancer - Drucker, Elisabeth; Pusch, Stefan; Herpel, Esther; Goeppert, Benjamin; Rössler, Stephanie; Schirmacher, Peter; Breuhahn, Kai (Cell communication and signaling, 2019)
Members of the karyopherin superfamily serve as nuclear transport receptors/adaptor proteins and provide exchange of macromolecules between the nucleo- and cytoplasm. Emerging evidence suggests a subset of karyopherins to be dysregulated in hepatocarcinogenesis including karyopherin-α2 (KPNA2). However, the functional and regulatory role of KPNA2 in liver cancer remains incompletely understood.
Gesehen am 27.01.2020